Conversation circle in a public clinic: the role of primary care in popular health education (Research, Society and Development, 2021)
Primary Health Care (APS), through humanized care, rescues the bonds of commitment between health services, professionals and the population, more effectively, through popular health education (EPS). The objective was to carry out, in the waiting room of a public clinic - Sette de Barros Ambulatory (ASB), a conversation circle (RCO), and describe the role of APS in EPS, as a source of accessible and safe information. After Ethics approval, opinion number 2,925,286, a printed questionnaire was applied to 378 people - number defined by finite sample calculation -, in September and November 2018. After the research identified the interest in participating in the ROC by 79, 62% of respondents, three ROCs were carried out, in the period between March and April 2019, with subsequent evaluation of the dialogic event. The research identified as the main positive points the easy understanding and the exchange of experiences, and as a negative aspect, mentioned by most, the very short time. APS plays a crucial role in providing information to users and is the main source of secure and easily accessible information. For this reason, the conversation wheel tool promotes EPS, being an important integrator of teaching-service-research. The population needs more moments of discussion with health professionals to demonstrate the knowledge gaps and enable a proposal for teaching-service integration, favoring the satisfaction and empowerment of users of the health actions provided by the ASB.